Are stromatolites in the northern Perth Basin following the End Permian mass extinction?. Issue 1 (1st December 2019) - Olden*, Liam J.; Cunneen, Jane; Barham, Milo; Olierook, Hugo K.H.; Smith, Gregory; Suosaari, Erica
Summary: Following the End Permian Mass Extinction (EPME) event, global stromatolite distributions rapidly increased. There are three documented examples of stromatolites occurring in intracontinental settings following the EPME; Greenland, Madagascar and west Australia's Northern Perth Basin. We are reporting the west Australian stromatolite occurrence to be much further than previously thought, through detailed mapping and analysis of stromatolites in the Northampton region. A review of the stromatolites show alternating stromatolite morphologies, with a minimum of four phases. These alternating morphologies are attributed to environmental changes in energy and detrital input, as well as microbe community induced structural changes. Two primary morphologies are documented, large smooth domal and micro-digitate structures. Using sedimentological characteristics of the conglomerates below and the stromatolite unit itself, a revised palaeo-environmental model is proposed for the growth of the stromatolitic unit. The model places the system in an intracontinental marine setting with shallow basinal margins defined by the mid-Palaeozoic Tumblagooda Sandstone. Mass flow deposits come in from the margins, defined by cobble conglomerates, on which the stromatolites grow. The stromatolites have previously been considered to be Early Triassic in age. However, revised stratigraphic relationships suggest they may be older than previously thought. Raising the question, do the northern Perth Basin stromatolites truly correlate with a mass extinction event?